Analysis the Effect of Sharia Monetary Operations (OMS) on Inflation in Indonesia for the 2019-2021 Period - Anggini, Karlita; Fitriyatustany, Fitriyatustany; Sari, Citra Atrina; Fitri, Resfa; Hasanah, Neneng (AL-MUZARA'AH, 2025)
Monetary policy is the government's effort to maintain, increase, or decrease the amount of money in circulation in order to sustain economic growth and combat inflation. Monetary policy in the form of Sharia Open Market Operations can be implemented by issuing Bank Indonesia Sharia Certificates (SBIS), Minimum Reserve Requirements (GWM), and Standing Facilities, such as Bank Indonesia Sharia Deposit Facilities (FASBIS). This study is novel because it uses comparative effectiveness analysis, different observation periods, and has undergone classical assumption testing. The purpose of this study is to describe and assess the effects of SBIS, FASBIS, and GWM on Indonesian inflation from 2019 to 2021. The research data is sourced from the Financial Services Authority (OJK) website. Multiple linear regression analysis was performed using the Eviews 10 software. The results showed that SBIS has no significant effect on inflation, FASBIS has a significant and negative effect on inflation, and GWM has a significant and positive effect on inflation. FASBIS and GWM can explain 79.7% of inflation, with other factors accounting for the remaining 20.3%. Islamic banking must improve its financial performance by utilizing FASBIS instruments more efficiently.